2018
DOI: 10.1029/2018sw001953
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time SWMF at CCMC: Assessing the Dst Output From Continuous Operational Simulations

Abstract: The ground-based magnetometer index of Dst is a commonly used measure of near-Earth current systems, in particular the storm time inner magnetospheric current systems. The ability of a large-scale, physics-based model to reproduce, or even predict, this index is therefore a tangible measure of the overall validity of the code for space weather research and space weather operational usage. Experimental real-time simulations of the Space Weather Modeling Framework (SWMF) are conducted at the Community Coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 130 publications
0
56
0
Order By: Relevance
“…Haiducek et al (2017) SYM-H prediction from SWMF for all of January 2005 R = 0.84, RMSE = 17 nT, ME = 4 nTLiemohn et al (2018) Dst prediction from SWMF in real-time mode R = 0.69, PE = 0.41, HSS = 0.57, RMSE = 13 nTMorley, Welling, and Woodroffe (2018) SYM-H prediction for the 5 April 2010 storm from an ensemble run varying solar wind input Probability distributions of MAE, ME, and RMSE 10.1029/2018SW002067…”
mentioning
confidence: 99%
“…Haiducek et al (2017) SYM-H prediction from SWMF for all of January 2005 R = 0.84, RMSE = 17 nT, ME = 4 nTLiemohn et al (2018) Dst prediction from SWMF in real-time mode R = 0.69, PE = 0.41, HSS = 0.57, RMSE = 13 nTMorley, Welling, and Woodroffe (2018) SYM-H prediction for the 5 April 2010 storm from an ensemble run varying solar wind input Probability distributions of MAE, ME, and RMSE 10.1029/2018SW002067…”
mentioning
confidence: 99%
“…The potential for improved forecasts has already been demonstrated for parts of the Sun-to-Earth system. For example, coupling a global magnetosphere model with an inner magnetosphere drift physics model considerably improves forecasts of geomagnetic storms (Liemohn et al, 2018) and improved representation of the thermosphere leads to improved ionospheric evolution (e.g., Chartier et al, 2013). In addition, there is a strong connection between the lower atmosphere state and the ionosphere that was highlighted initially by Immel et al (2006) and demonstrated in later modeling studies (e.g., Pedatella et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…from the NOAA solar wind predictions of the Wang-Sheeley-Arge(WSA)-ENLIL model (Parsons et al, 2011), from the Space Weather Modeling Framework (SWMF) (e.g. Haiducek et al, 2017;Liemohn et al, 2018;Wintoft and Wik, 2018) or from the SWIFT-code (Arber et al, 2001).…”
Section: Discussionmentioning
confidence: 99%